2020
DOI: 10.1186/s12879-020-05332-9
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence ptxP3 lineage of Bordetella pertussis was rare in young children with the co-purified aPV vaccination: a 5 years retrospective study

Abstract: Background: The global prevalent ptxP3 strains varies from about 10% to about 50% of circulating B. pertussis population in different areas of China. Methods: To investigate the difference of vaccination status between different genotypes in the circulating B. pertussis after 10 years of acellular pertussis vaccine (aPV) used in China. The nasopharyngeal swabs and isolates of B. pertussis from these patients were used to perform genotyping of antigen genes. We use antibiotic susceptibility test against erythro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…MRBPs in China was thought less likely to cause epidemics in other countries because the MRBPs in China were mostly assigned to ptxP1 lineage, whereas ptxP3 strains are currently endemic in other countries ( 21 , 27 ). In China, ptxP1 -MRBPs were reported to contribute 75.4% (Zhejiang Province, 2016), 48.6% (Shenzhen Province, 2015–2017), and 84.9% (a multicenter study during 2017–2019) of the circulating B. pertussis strains in China ( 15 , 41 , 42 ). Previous studies showed that MRBP was mostly linked to the ptxP1 allele and that the ptxP3 strain was isolated from MSBP without exception ( 6 , 20 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRBPs in China was thought less likely to cause epidemics in other countries because the MRBPs in China were mostly assigned to ptxP1 lineage, whereas ptxP3 strains are currently endemic in other countries ( 21 , 27 ). In China, ptxP1 -MRBPs were reported to contribute 75.4% (Zhejiang Province, 2016), 48.6% (Shenzhen Province, 2015–2017), and 84.9% (a multicenter study during 2017–2019) of the circulating B. pertussis strains in China ( 15 , 41 , 42 ). Previous studies showed that MRBP was mostly linked to the ptxP1 allele and that the ptxP3 strain was isolated from MSBP without exception ( 6 , 20 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 2 types of diphtheria, tetanus, and pertussis (DTaP) vaccine formulations are licensed in China: one is the 2-component DTaP vaccine containing PT and FHA, another is the 3-component DTaP vaccine containing PT, FHA, and PRN ( 43 ). The circulating B. pertussis has evolved, mainly changed from ptxP1 to ptxP3 lineage, indicating the ptxP3 variation reflect selective advantage under high coverage with acellular pertussis vaccine ( 42 ). Previous study showed that prn2 variation affected the efficacy of commercial vaccine, and mice studies suggested that the incorporation of prn2 to vaccine could enhance the ACV’s efficacy ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the recent emergence and spread of a new Bordetella variant, genetic variation has become a major concern regarding vaccine efficacy [ 54 , 55 ]. Nowadays, the ptxP3 strains, reported to be more virulent as suggested by increased pertussis toxin production, indicate selective advantage under vaccine mediated selection pressure [ 56 , 57 ]. Therefore, current whole-cell and acellular vaccine efficacy should be evaluated against strains carrying the ptxP3 allele type [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, macrolide resistance in B. pertussis in China has been associated almost exclusively with the ptxP1 lineage of the bacterium [ 22 , 27 , 29 , 30 , 31 , 32 , 37 ]. However, a recent cross-sectional study describes two ptxP3 isolates from eastern China that had acquired the A2047G mutation in their 23S rRNA gene [ 40 ].…”
Section: Epidemiologymentioning
confidence: 99%